(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The repeatability of three-dimensional printers is very important because it determines how accurately a model can be reproduced. Repeatability depends on many factors such as printer quality, software settings, material quality, etc This paper evaluates the repeatability of an Openware desktop three dimensional printers in terms of the resulting standard deviation from a set of samples using a multi-sensor measuring machine. Details with optimal parameters were printed. Statistical analysis was performed on this set of samples. From the statistical analysis of the dimensional deviation data, the repeatability of the printer was analyzed.